Application of the Jigsaw Cooperative Learning Model Oriented Towards Improving High School Student Learning Outcomes - Suparwati, Sri (Journal of Education Action Reseach, 2024)
The problem often encountered in learning is students' low motivation and learning outcomes. This is caused by learning that does not provide opportunities for students to improve their thinking and argumentation skills. This study aims to apply the Jigsaw-Oriented Cooperative Learning Model to the Learning Outcomes of High School Students. This type of research is class action research. The Classroom Action Research used in this study is a model developed by Kemmis and McTaggart. The Classroom Action Research was conducted in two cycles, each with 2 meetings. The number of students involved was 36, consisting of 22 (61%) female and 14 (39%) male. Data collection methods used observation, interviews, and tests. The instruments used to assess students' physics learning outcomes in each cycle were multiple-choice questions. Data was analyzed using qualitative and quantitative descriptive analysis. The study results show that after two research cycles, actions were carried out that showed an increase in student learning outcomes, individually and collectively. The average student learning outcomes increased from 79.8 to 81.1. The number of students who completed was 75% to 83.3%. Therefore, using a cooperative learning paradigm such as Jigsaw can improve students' understanding of physics. It is concluded that the Jigsaw Type Cooperative Learning Model can improve the learning outcomes of high school students.